2014
DOI: 10.3109/14767058.2014.969236
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C in newborns: a promising renal biomarker in search for standardization and validation

Abstract: Objective Neonatologists still commonly use creatinine as a proxy for renal clearance, despite issues related to neonatal (patho)physiology and methodology (assay variability). Cystatin C (CysC) has been suggested to be a more reliable biomarker, but assay related differences have also been reported in children and adults. We are unaware of any review on the assay related impact on CysC reference values in newborns. Methods A structured literature search was performed on published CysC values in (pre)term ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 40 publications
1
40
0
5
Order By: Relevance
“…The role of some core proteins in the kidney and urinary tract function of adults and children was previously discussed [33][34][35][36][37][38]. EGF participates in renal development, a postnatal rise in renal EGF content and urinary EGF excretion suggests a role of EGF in renal maturation [38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of some core proteins in the kidney and urinary tract function of adults and children was previously discussed [33][34][35][36][37][38]. EGF participates in renal development, a postnatal rise in renal EGF content and urinary EGF excretion suggests a role of EGF in renal maturation [38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cystatin C is mainly used as a biomarker of kidney function and glomerular filtration rate (GFR) [34][35][36] and its level was shown to be higher in preterm as compared to term neonates [33]. Retinol-binding protein is a low molecular weight protein of 21 kDa that transports retinol from the liver to peripheral tissues.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies, however, have shown that S-CysC is more useful biomarker for renal function than S-Cr even in children including neonates [23][24][25]. Furthermore, unlike Cr, CysC does not cross the placenta; therefore, the CysC levels may reflect renal function of the neonates even at the first day of life [26,27] though only few studies have examined S-CysC levels in this period [5][6][7].…”
Section: Discussionmentioning
confidence: 95%
“…In adults, serum cystatin C (S-CysC), which is less influenced by extrarenal factors, is being used as a sensitive biomarker for renal function [3,4]. The same has not been extensively studied in the early neonatal period [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Allegaert і співавтори у пошуках стандарти-зації і валідації перспективного біомаркера нирок цистатину С визначили, що його застосування в неонатальній медицині може бути додатково по-кращено за рахунок використання конкретних контрольних значень, адаптованих до неонаталь-ної ниркової фізіології [3].…”
Section: том 6 № 4 2017unclassified